Ground-state flavin-dependent enzymes catalyzed enantioselective radical trifluoromethylation - Xinyu Duan; Dong Cui; Mengdi Wang; Chenlu Jin; Xiaochen Cai; Zhiguo Wang; Jian Xu (Nature Communications)
Abstract The introduction of fluoroalkyl groups into pharmaceutical compounds has the potential to enhance their therapeutic properties. Nevertheless, the synthesis of enantiomerically pure C(sp³)–CF₃ compounds poses a significant challenge. Biocatalysis offers precise stereochemical control, however, the scarcity of fluorine-containing natural products makes it difficult to find enzymes capable of incorporating fluoroalkyl groups. Herein, we develop a ground-state flavin-dependent enzyme-catalyzed strategy for the radical-mediated enantioselective trifluoromethylation. Two engineered flavin-dependent enzymes are successfully developed to catalyze stereoselective hydrotrifluoromethylation and trifluoromethyl-alkyl cross-electrophile coupling reactions using trifluoromethyl thianthrenium triflate as a radical donor. Experimental investigations and computational simulations demonstrate that the reaction is initiated through single-electron transfer from the ground state flavin hydroquinone (FMNhq) and quenched through hydrogen atom transfer by flavin semiquinone (FMNsq). This strategy provides an opportunity to bridge the gap between biocatalysis and organic fluorides but also introduces an alternative approach to address challenging stereoselective fluoroalkylation reactions in organic synthesis.